Diel patterns and migration behaviour of sympatric Atlantic salmon (Salmo salar) and brown trout (Salmo trutta) smolts during seaward migration - Ulvund, John Birger; Smalås, Aslak; Strand, Rita; Lamberg, Anders (Frontiers in Marine Science, 2025)
Migrations between different habitats to maximise fitness are well documented in many organisms, although such migrations imply a potentially great risk when moving between habitats. For anadromous salmonids, these migrations occur between the freshwater stage in their natal rivers to coastal waters during spring/summer, where they can potentially experience high mortality rates. This study investigated the riverine migration dynamics of Atlantic salmon (Salmo salar) and sea trout (Salmo trutta) smolts with a multiple camera array over three consecutive years (2021–2023). A total of 19,238 individuals were recorded, and the dynamics of schooling behaviour and diel activity patterns were examined with respect to both intra- and interspecific traits associated with migratory behaviour. The observed pattern describes the migration dynamics for sympatric natural stocks of Atlantic salmon and sea trout over a 3-year period with little-to-no interferences with natural behaviour. Results indicate a clear diel pattern in schooling behaviour, governed by the influx of natural light, with clear species-specific differences in migratory behaviour. The observed diel pattern was less dominant later in the migration period, revealing daylight length as a factor altering migratory behaviour during the smolt run. The observed changes in migration dynamics could possibly be adapted as an anti-predator behaviour during river migration, where night/dark offers protection from visual predators, whereas safety in numbers aids predator detection and avoidance during daytime.